Revamping Partnership Agreements to Empower Micro, Small, and Medium Enterprises in the Processed Marine Fish Food Industry - Badriyah, Siti Malikhatun; R. Suharto; Retno Saraswati; Marjo (Lentera Hukum, 2025)
Due to its abundant resources, Indonesia holds significant potential for developing its processed food industry using marine fish as a raw material. Micro, Small, and Medium Enterprises (MSMEs) are central to this sector. However, these enterprises need more capital, knowledge, technology, and marketing, distribution, and licensing. Therefore, collaboration with larger business entities through partnership systems is crucial. Currently, the legal relationships within these partnerships are based on agreements, but specific regulations often lead to imbalanced relationships between the parties involved. This research emphasizes the need to reconstruct regulations on partnership agreements to foster MSME development in the processed food industry. The government should conduct comprehensive socialization in collaboration with various stakeholders, including business actors, community leaders, and academics, to educate MSMEs and large business actors about the importance of business partnerships and their legal aspects. The legislative body should also formulate specific regulations to provide balanced legal protection for all parties involved.Keywords: MSMEs, Processed Food, Business Partnership, Agreement, Regulation.